Evaluation of PCR‐HRM, RFLP, and direct sequencing as simple and cost‐effective methods to detect common EGFR mutations in plasma cell–free DNA of non–small cell lung cancer patients. Issue 4 (3rd February 2019) - Zaini, Jamal; Syahruddin, Elisna; Yunus, Muhammad; Andarini, Sita Laksmi; Hudoyo, Achmad; Masykura, Najmiatul; Yasril, Refniwita; Ridwanuloh, Asep; Hidajat, Heriawaty; Nurwidya, Fariz; Suharsono, Sony; Utomo, Ahmad R.H.
Abstract: Background: Lung cancer patients with mutations in epidermal growth factor receptor ( EGFR ) gene are treated with tyrosine kinase inhibitor (TKI). Aims: We aimed to evaluate polymerase chain reaction (PCR)–high‐resolution melting (HRM), restriction fragment length polymorphism (RFLP), and direct sequencing (DS) to detect EGFR mutations in cell‐free DNA (cfDNA) before and after TKI treatment in real‐world settings of a developing country. Methods: Paired cytology and plasma samples were collected from 116 treatment‐naïve lung cancer patients. DNA from both plasma and cytology specimens was isolated and analyzed using PCR‐HRM (to detect exon 19 insertion/deletion), RFLP (to genotypes L858R and L861Q), and DS (to detect uncommon mutations G719A, G719C, or G719S [G719Xaa] in exon 18 and T790M and insertion mutations in exon 20). Results: EGFR genotypes were obtained in all 116 (100%) cfDNA and 110/116 (94.82%) of cytological specimens of treatment‐naïve patient (baseline samples). EGFR ‐activating mutations were detected in 46/110 (40.6%) plasma samples, and 69/110 (63.2%) mutations were found in routine cytology samples. Using cytological EGFR genotypes as reference, we found that sensitivity and specificity of baseline plasma EGFR testing varied from 9.1% to 39.39% and 83.12% to 96.55%, respectively. In particular, the sensitivity and specificity of this assay in detecting baseline T790M mutations in exon 20 were 30% and 89.58%, respectively. Three months after TKI treatment, plasma T790M and insertion exon 20 mutations appeared in 5.4% and 2.7% patients, respectively. Conclusions: Despite low sensitivity, combined DS, RFLP, and PCR‐HRM was able to detect EGFR mutations in plasma cfDNA with high specificity. Moreover, TKI resistance exon 20 insertions mutation was detected as early as 3 months post TKI treatment.